The Content of Developing Students' Spatial Imaginations Through STEM Education - So'fiboyeva Gulchexra Mamurjanovna (Scientific Trends, 2024)
In this article, preliminary manifestations of the development of spatial imaginations are determined in preschool and primary education, taking into account the young age of a child in a row.